2021
DOI: 10.1051/shsconf/20219207021
|View full text |Cite
|
Sign up to set email alerts
|

Actual problems and limiting factors in the development of the Russian military-industrial complex

Abstract: Research background: The completion of the ideological confrontation of socio-economic systems that occurred in the early 90s of XX century after the collapse of the USSR did not radically affect the development of the global defense industrial complex (DIC). Taking into account the place and role of national DICs in the economies of the world’s leading powers, we can only talk about the modification of their development in the new historical conditions. The defense industry complex in Russia, as before in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Despite the presence of certain problems in the functioning of the Russian militaryindustrial complex (Gregova et al, 2021), overall, the recent reforms carried out can be considered successful. During the period under review, most of the companies in the Russian defense industry have shown cumulative growth in financial performance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of certain problems in the functioning of the Russian militaryindustrial complex (Gregova et al, 2021), overall, the recent reforms carried out can be considered successful. During the period under review, most of the companies in the Russian defense industry have shown cumulative growth in financial performance.…”
Section: Discussionmentioning
confidence: 99%
“…They have long formed multi-sectoral military-industrial complexes (MIC), spend huge sums on military spending, have long and successfully produced the entire range of military equipment, a significant part of which is supplied to the world market. Their positions on the world market, the share of the total volume of arms sales, the circle of buyers of their products is sufficient stable (Dengov et al, 2021;Gregova et al, 2021). Weapons are long-term and expensive products.…”
Section: Introductionmentioning
confidence: 99%